The Controversial Relationship Between Economic Growth and Human Dignity - Faccini, Niccolo (UNWE Yearbook, 2024)
The relationship between economic growth and human dignity is a topic of great philosophical and ethical importance. Although economic growth can lead to an improvement in material living conditions, in many cases it can also lead to the violation of people’s fundamental rights, such as the right to decent work, health and education. Moral philosophy – in the wake of the Kantian lesson according to which every man should be treated as an end and not as a mere instrument – asks to consider the intrinsic value of the human being and to place human rights at the heart of ethical reflection.